Meningkatkan Keterampilan Berpikir Kritis Melalui Pembelajaran Kritis - Abd Rahim (Saba Jaya Publisher, 2023)
This research aims to examine the improvement of students' critical thinking skills through the implementation of the Merdeka Belajar Curriculum in mathematics and science education. The process skills approach is implemented with a focus on utilizing digital media, specifically contextual-based flipbooks. In the context of mathematics and science learning, the low critical thinking skills of students are identified, possibly influenced by the dominant conventional memorization-based teaching methods. The research results indicate that the Merdeka Belajar Curriculum can contribute positively to the improvement of students' grades, especially in the aspect of critical thinking. The implementation of digital media, such as flipbooks, proves to be effective in stimulating students' interest and understanding of science subjects. Evaluation of assessment results shows a significant improvement in students' critical thinking skills after implementing the Merdeka Belajar Curriculum. These findings emphasize the need for further focus on integrating critical thinking into teaching practices, utilizing digital media, and implementing a curriculum that supports creativity and independence to achieve optimal progress in the field of education.